Nylon material capable of being subjected to laser welding and preparation method thereof
By adding enhanced transparent modified nylon and modified glass fiber to nylon materials and adopting specific preparation methods, the problem of insufficient laser transmittance and light absorption capacity of nylon materials is solved, and the high laser transmittance and welding strength is improved, and the field of high transmittance requirements is met.
Patent Information
- Application Number
- CN202411937592.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to improve the laser transmittance and light absorption capacity of nylon materials, resulting in insufficient strength at the welding point after laser welding and unable to meet the usage requirements.
By adding modified nylon and modified glass fibers to the nylon material, and using specific preparation methods, including the complex coordination reaction between calcium chloride, maleic anhydride grafted POE and nylon, it shields hydrogen bonds in nylon, hinders crystallization, and improves laser transmittance.
It realizes high laser transmittance and strength of nylon materials, improves welding quality, and meets areas with high requirements for material light transmittance.
Smart Images

Figure BDA0005211864810000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer technology, in particular to a laser-weldable nylon material and a preparation method thereof. Background Art
[0002] Polyamide has excellent mechanical and physical properties and is widely used in machinery manufacturing, power tools, electronic appliances, transportation and other fields. Reinforced and toughened polyamide materials are the preferred materials for functional structural parts. For many complex parts containing branches or joints, it is difficult to obtain them in one step through traditional injection molding methods, and welding technology is required for assembly. At present, most nylon materials can meet the technical requirements of vibration welding, while nylon materials that can be laser welded are still in the initial stage of development, and there are some technical barriers waiting for us to overcome. The main difficulty is to increase the transmittance of the light-transmitting layer nylon and the light-absorbing ability of the light-absorbing layer nylon, so as to ensure the strength of the weld after laser welding. Generally speaking, polyamide resin, conventional resin and glass fiber basically do not absorb commercial near-infrared laser (wavelength 950-1064nm), but the microscopic phase interface between several components will change the refractive index of the laser, resulting in increased light scattering; the commonly used inorganic black toner is a very good light absorber, and has very strong absorption of near-infrared laser, making it difficult for the laser to penetrate the light-transmitting layer to reach the welding interface, resulting in poor laser weldability of black reinforced toughened polyamide materials, or low welding strength, which cannot meet the use requirements. Current research on laser welding is mainly focused on light-colored modified polyamide materials, and there is no mature technical solution for black reinforced toughened polyamide materials with high laser welding strength.
[0003] In Chinese patents CN111875957A and CN111849152, magnesium and aluminum compounds are used to improve the laser welding ability of polyamide materials, but the high loss of laser energy by the black light-transmitting layer cannot be solved. In actual experiments, it is found that the welding effect of black products is not ideal. In Chinese patent application CN112724668A, a wide molecular weight distribution polyamide 66 resin is selected, and carbon black with -COOH group modified on the surface is added to obtain a polyamide composition with high surface gloss and high light transmittance, which is suitable for laser welding. A good surface can indeed reduce the energy loss of laser in disordered refraction, but the absorption of laser by modified carbon black is still too strong, which affects the welding quality.
[0004] Therefore, the development of black reinforced and toughened polyamide composites with high laser welding strength has great market significance and economic value. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a laser-weldable nylon material and a preparation method thereof, which maintains the mechanical properties of the material while having a high laser transmittance.
[0007] (II) Technical solution
[0008] A laser weldable nylon material comprises the following raw materials in parts by weight:
[0009] 33-67 parts of nylon, 10-30 parts of anti-reflective modified nylon, 20-30 parts of modified glass fiber, 2-5 parts of compatibilizer, and 1-2 parts of additive.
[0010] Preferably, the nylon is PA6, PA66 or a mixture thereof, and the relative viscosity of the nylon is 2.7.
[0011] Preferably, the preparation method of the anti-reflection modified nylon is as follows:
[0012] PA6 was placed in an oven at 100°C and dried for 8 h. 2 Place in an oven at 120°C and air dry for 4 hours. After drying, 92 parts of PA6 and 5 parts of CaCl 2 Premix it evenly with 3 parts of POE-g-MAH and 1 part of antioxidant in a high-speed mixer, and then feed it into a twin-screw extruder. The temperature of the extruder from the feeding section to the die is set to 200°C, 240°C, 240°C, 240°C, and 250°C, the screw speed is 300r / min, and extrusion and pelletizing are performed.
[0013] Preferably, the preparation method of the modified glass fiber is as follows:
[0014] The glass fiber is placed in a hydrofluoric acid solution containing 1-3% by mass, maintaining a liquid-to-solid ratio of 10-15:1, soaked at 20-30°C for 30-60 minutes, washed with deionized water until neutral, dried, and then soaked in a 5-10% by mass ammonium fluoride solution, stirred and reacted for 2-4 hours under 40-60°C water bath heating conditions, washed with deionized water until neutral, and dried to obtain the product.
[0015] Preferably, the compatibilizer is POE-g-MAH.
[0016] Preferably, the auxiliary agent includes 0.5-1 part of antioxidant and 0.5-1 part of lubricant.
[0017] Preferably, the antioxidant is antioxidant 1098, antioxidant 1076 or antioxidant 168.
[0018] Preferably, the lubricant is selected from one or more of stearic acid, stearic acid amide, oleic acid amide or lubricant EBS.
[0019] Preferably, the method comprises the following steps:
[0020] S1, adding nylon resin, anti-permeability modified nylon, compatibilizer and additive into a high-speed mixer and mixing for 15-20 minutes, and obtaining a mixed raw material after mixing evenly;
[0021] S2, adding the mixture obtained in step S1 to a co-rotating twin-screw extruder for extrusion granulation, adopting a melt blending extrusion process, adding a blend of nylon resin, anti-permeability modified nylon, compatibilizer and processing aid from the main feed port, adding modified glass fiber from the side feed port, and after melt blending, cooling, air drying and granulation, the mixture is obtained.
[0022] Preferably, the temperature of each zone of the twin-screw extruder is as follows: zone 1 temperature 150-230°C, zone 2 temperature 180-265°C, zone 3 temperature 190-275°C, zone 4 temperature 200-280°C, zone 5 temperature 200-280°C, zone 6 temperature 200-280°C, die head temperature 200-280°C; vacuum is turned on, speed is 250-350r / min
[0023] (III) Beneficial technical effects
[0024] The preparation method of the laser-weldable nylon material provided by the present invention is to add anti-transmittance modified nylon to glass fiber reinforced polyamide resin, and the anti-transmittance modified nylon is prepared by complexing and coordinating calcium chloride, maleic anhydride grafted POE and nylon, and the complexing and coordinating can shield the hydrogen bonds between amide molecules, hinder the crystallization of nylon, reduce the crystallinity of nylon 6, and make it a transparent amorphous state, thereby improving the laser transmittance of the reinforced polyamide material. After the glass fiber is treated by the modification process, the laser transmittance is significantly improved, the internal stress is significantly reduced, and the structural stability is improved, laying the foundation for the expansion of glass fiber to the high-end optical field. At the same time, a compatibilizer is added to improve the compatibility with PA and glass fiber, so that the composition has excellent mechanical properties, which is particularly suitable for the field of laser welding and the field with high requirements for material transmittance. DETAILED DESCRIPTION
[0025] The following are the relevant commercially available or supplier-provided raw materials specifically used in the embodiments of the present invention and the comparative examples, but are not limited to the following raw materials: Nylon 6 2702BR: Tianjin Changlu Haijing Group Co., Ltd., with a relative viscosity of 2.7; anti-reflective modified nylon: homemade; glass fiber: Chongqing International Composite Materials Co., Ltd., with an effective monofilament diameter of 15-17um, a short-side monofilament diameter of 6-8um, a glass fiber length of 3mm, and homemade modified glass fiber; compatibilizer POE-g-MAH: N413A, Ningbo Nengzhiguang New Materials Technology Co., Ltd., with a grafting rate of 1%; additives are antioxidant 1098 BASF of Germany, antioxidant 168 Beijing Jiyi Chemical Co., Ltd., and lubricant EBS Kao of Japan.
[0026] The present invention is further described below by means of specific embodiments, which are only used to illustrate the present invention rather than to limit the present invention.
[0027] Example 1
[0028] A laser weldable nylon material comprises the following raw materials in parts by weight: 67 parts of nylon 6, 10 parts of anti-reflective modified nylon, 20 parts of modified glass fiber, 2 parts of a compatibilizer, 0.3 parts of an antioxidant 1098, 0.2 parts of an antioxidant 168, and 0.5 parts of a lubricant EBS;
[0029] The preparation method of anti-reflection modified nylon is as follows:
[0030] PA6 was placed in an oven at 100°C and dried for 8 h. 2 Place in an oven at 120°C and air dry for 4 hours. After drying, 92 parts of PA6 and 5 parts of CaCl 2 Premix it evenly with 3 parts of POE-g-MAH and 1 part of antioxidant in a high-speed mixer, and then feed it into a twin-screw extruder. The temperature of the extruder from the feeding section to the die is set to 200°C, 240°C, 240°C, 240°C, and 250°C, the screw speed is 300r / min, and extrusion and pelletizing are performed.
[0031] The preparation method of modified glass fiber is as follows:
[0032] The glass fiber is placed in a 1% hydrofluoric acid solution with a liquid-to-solid ratio of 10:1, immersed at 20°C for 30 minutes, washed with deionized water until neutral, dried, immersed in a 5% ammonium fluoride solution, stirred and reacted for 2 hours in a 40°C water bath, washed with deionized water until neutral, and dried to obtain the product.
[0033] The specific preparation method comprises the following steps:
[0034] Add nylon, anti-permeability modified nylon, compatibilizer and auxiliary agent into a high-speed mixer, stir and mix for 10 minutes until uniform, to obtain a mixture; add the mixture into the main feeding port of a co-rotating twin-screw extruder, feed the modified glass fiber from the side feeding port, control the screw speed to 300r / min, the temperature of zone 1 to 150°C, the temperature of zone 2 to 180°C, the temperature of zone 3 to 190°C, the temperature of zone 4 to 200°C, the temperature of zone 5 to 200°C, the temperature of zone 6 to 200°C, the temperature of the die head to 200°C, melt-blending and extruding, cooling, and pelletizing to obtain the laser-weldable nylon material.
[0035] Example 2
[0036] A laser weldable nylon material comprises the following raw materials in parts by weight: 62 parts of nylon 6, 15 parts of anti-reflective modified nylon, 20 parts of modified glass fiber, 2 parts of a compatibilizer, 0.3 parts of an antioxidant 1098, 0.2 parts of an antioxidant 168, and 0.5 parts of a lubricant EBS;
[0037] The preparation method of anti-reflection modified nylon is as follows:
[0038] PA6 was placed in an oven at 100°C and dried for 8 h. 2 Place in an oven at 120°C and air dry for 4 hours. After drying, 92 parts of PA6 and 5 parts of CaCl 2 Premix it evenly with 3 parts of POE-g-MAH and 1 part of antioxidant in a high-speed mixer, and then feed it into a twin-screw extruder. The temperature of the extruder from the feeding section to the die is set to 200°C, 240°C, 240°C, 240°C, and 250°C, the screw speed is 300r / min, and extrusion and pelletizing are performed.
[0039] The preparation method of modified glass fiber is as follows:
[0040] The glass fiber is placed in a 3% by mass hydrofluoric acid solution with a liquid-to-solid ratio of 15:1, immersed at 30°C for 60 minutes, washed with deionized water until neutral, dried, immersed in a 10% by mass ammonium fluoride solution, stirred and reacted for 4 hours in a 60°C water bath, washed with deionized water until neutral, and dried to obtain the product.
[0041] The specific preparation method comprises the following steps:
[0042] Add nylon, anti-permeability modified nylon, compatibilizer and auxiliary agent into a high-speed mixer and stir and mix for 10 minutes until uniform to obtain a mixture; add the mixture into the main feeding port of a co-rotating twin-screw extruder, feed the modified glass fiber from the side feeding port, control the screw speed to 300r / min, the temperature of zone 1 to 230°C, the temperature of zone 2 to 265°C, the temperature of zone 3 to 275°C, the temperature of zone 4 to 280°C, the temperature of zone 5 to 280°C, the temperature of zone 6 to 280°C, the temperature of the die head to 280°C, melt-blending and extruding, cooling, and pelletizing to obtain the laser-weldable nylon material.
[0043] Example 3
[0044] A laser weldable nylon material comprises the following raw materials in parts by weight: 57 parts of nylon 6, 20 parts of anti-reflective modified nylon, 20 parts of modified glass fiber, 2 parts of a compatibilizer, 0.3 parts of an antioxidant 1098, 0.2 parts of an antioxidant 168, and 0.5 parts of a lubricant EBS;
[0045] The preparation method of anti-reflection modified nylon is as follows:
[0046] PA6 was placed in an oven at 100°C and dried for 8 h. 2 Place in an oven at 120°C and air dry for 4 hours. After drying, 92 parts of PA6 and 5 parts of CaCl 2 Premix it evenly with 3 parts of POE-g-MAH and 1 part of antioxidant in a high-speed mixer, and then feed it into a twin-screw extruder. The temperature of the extruder from the feeding section to the die is set to 200°C, 240°C, 240°C, 240°C, and 250°C, the screw speed is 300r / min, and extrusion and pelletizing are performed.
[0047] The preparation method of modified glass fiber is as follows:
[0048] The glass fiber is placed in a 2% by mass hydrofluoric acid solution with a liquid-to-solid ratio of 12:1, immersed at 25°C for 40 minutes, washed with deionized water until neutral, dried, immersed in a 6% by mass ammonium fluoride solution, stirred and reacted for 3 hours in a 50°C water bath, washed with deionized water until neutral, and dried to obtain the product.
[0049] The specific preparation method comprises the following steps:
[0050] Add nylon, anti-permeability modified nylon, compatibilizer and auxiliary agent into a high-speed mixer and stir and mix for 10 minutes until uniform to obtain a mixture; add the mixture into the main feeding port of a co-rotating twin-screw extruder, feed the modified glass fiber from the side feeding port, control the screw speed to 300r / min, the temperature of zone 1 to 180°C, the temperature of zone 2 to 200°C, the temperature of zone 3 to 210°C, the temperature of zone 4 to 230°C, the temperature of zone 5 to 250°C, the temperature of zone 6 to 260°C, the temperature of the die to 280°C, melt-blending and extruding, cooling, and pelletizing to obtain the laser-weldable nylon material.
[0051] Example 4
[0052] A laser weldable nylon material comprises the following raw materials in parts by weight: 33 parts of nylon 6, 30 parts of anti-reflective modified nylon, 30 parts of modified glass fiber, 5 parts of a compatibilizer, 0.6 parts of an antioxidant 1098, 0.4 parts of an antioxidant 168, and 1 part of a lubricant EBS;
[0053] The preparation method of anti-reflection modified nylon is as follows:
[0054] PA6 was placed in an oven at 100°C and dried for 8 h. 2 Place in an oven at 120°C and air dry for 4 hours. After drying, 92 parts of PA6 and 5 parts of CaCl 2Premix it evenly with 3 parts of POE-g-MAH and 1 part of antioxidant in a high-speed mixer, and then feed it into a twin-screw extruder. The temperature of the extruder from the feeding section to the die is set to 200°C, 240°C, 240°C, 240°C, and 250°C, the screw speed is 300r / min, and extrusion and pelletizing are performed.
[0055] The preparation method of modified glass fiber is as follows:
[0056] The glass fiber is placed in a 3% by mass hydrofluoric acid solution with a liquid-to-solid ratio of 13:1, immersed at 25°C for 50 minutes, washed with deionized water until neutral, dried, immersed in an 8% by mass ammonium fluoride solution, stirred and reacted for 3 hours in a 50°C water bath, washed with deionized water until neutral, and dried to obtain the product.
[0057] The specific preparation method comprises the following steps:
[0058] Add nylon, anti-permeability modified nylon, compatibilizer and auxiliary agent into a high-speed mixer and stir and mix for 10 minutes until uniform to obtain a mixture; add the mixture into the main feeding port of a co-rotating twin-screw extruder, feed the modified glass fiber from the side feeding port, control the screw speed to 300r / min, the temperature of zone 1 to 150°C, the temperature of zone 2 to 180°C, the temperature of zone 3 to 250°C, the temperature of zone 4 to 220°C, the temperature of zone 5 to 260°C, the temperature of zone 6 to 280°C, the temperature of the die to 280°C, melt-blending and extruding, cooling, and pelletizing to obtain the laser-weldable nylon material.
[0059] Comparative Example 1
[0060] Comparative Example 1 is a comparative example of Example 1, including the following raw materials in parts by weight: 77 parts of nylon 6, 20 parts of modified glass fiber, 2 parts of compatibilizer SEBS-g-MAH, 0.3 parts of antioxidant 1098, 0.2 parts of antioxidant 168, and 0.5 parts of lubricant EBS; the specific preparation method is the same as that of Example 1.
[0061] Comparative Example 2
[0062] Comparative Example 2 is a comparative example of Example 4, including the following raw materials in parts by weight: 63 parts of nylon 6, 30 parts of modified glass fiber, 5 parts of compatibilizer SEBS-g-MAH and 2 parts of auxiliary agent; the specific preparation method is the same as that of Example 4.
[0063] Comparative Example 3
[0064] Comparative Example 3 is a comparative example of Example 2, including the following raw materials in parts by weight: 62 parts of nylon 6, 20 parts of modified glass fiber, 15 parts of transparent nylon, 2 parts of compatibilizer, 0.3 parts of antioxidant 1098, 0.2 parts of antioxidant 68, and 0.5 parts of lubricant EBS; the specific preparation method is the same as that of Example 2.
[0065] Comparative Example 4
[0066] Comparative Example 3 is a comparative example of Example 1, including the following raw materials in parts by weight: 67 parts of nylon 6, 10 parts of anti-permeability modified nylon, 2 parts of compatibilizer, 0.3 parts of antioxidant 1098, 0.2 parts of antioxidant 168, and 0.5 parts of lubricant EBS; the specific preparation method is the same as that of Example 2.
[0067] The laser weldable nylon materials prepared in the above Examples 1-4 and Comparative Examples 1-3 were tested for tensile strength, flexural strength, notched impact strength according to ISO standards, and laser transmittance: tested using a Shanghai Shizhan TR-500 laser transmittance tester with a laser wavelength of 960 nm. The test results are listed in Table 1.
[0068] Table 1 Test results of Examples 1-4 and Comparative Examples 1-3
[0069]
[0070]
[0071] It can be concluded from Table 1 that by comparing Example 1 with Comparative Example 1 and Example 4 with Comparative Example 2, it can be seen that by adding anti-reflection modified nylon, the material has good mechanical properties and improves the laser transmittance. By comparing Examples 1, 2, 3, and 4, it can be seen that with the increase in the content of anti-reflection modified nylon, the laser transmittance continues to increase, the material notched impact strength increases, and the tensile strength and bending strength decrease slightly. By comparing Example 2 with Comparative Example 3, it can be seen that transparent nylon can improve the laser transmittance of the polyamide composition, but by adding transparent nylon, compared with adding anti-reflection modified nylon, the mechanical properties of the transparent nylon-modified composition are low, and the laser transmittance is also slightly low. By comparing Example 1 with Comparative Example 4, it can be seen that the modified glass fiber can improve the laser transmittance of the composite material and improve the structural strength.
[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A laser weldable nylon material, characterized in that: It includes the following raw materials in parts by weight: 33-67 parts of nylon, 10-30 parts of anti-reflective modified nylon, 20-30 parts of modified glass fiber, 2-5 parts of compatibilizer, and 1-2 parts of additive.
2. The laser weldable nylon material according to claim 1, characterized in that: The nylon is PA6, PA66 or a mixture thereof, and the relative viscosity of the nylon is 2.
7.
3. The laser weldable nylon material according to claim 1, characterized in that: The preparation method of the anti-reflection modified nylon is as follows: PA6 was placed in an oven at 100°C for 8 hours and anhydrous CaCl2 was placed in an oven at 120°C for 4 hours. After drying, 92 parts of PA6 and 5 parts of CaCl2 were pre-mixed with 3 parts of POE-g-MAH and 1 part of antioxidant in a high-speed mixer and then sent to a twin-screw extruder. The temperature of the extruder from the feeding section to the die was set to 200°C, 240°C, 240°C, 240°C, and 250°C, the screw speed was 300r / min, and extrusion and pelletizing were performed.
4. The laser weldable nylon material according to claim 1, characterized in that: The preparation method of the modified glass fiber is as follows: The glass fiber is placed in a hydrofluoric acid solution containing 1-3% by mass, maintaining a liquid-to-solid ratio of 10-15:1, soaked at 20-30°C for 30-60 minutes, washed with deionized water until neutral, dried, and then soaked in a 5-10% by mass ammonium fluoride solution, stirred and reacted for 2-4 hours under 40-60°C water bath heating conditions, washed with deionized water until neutral, and dried to obtain the product.
5. The laser weldable nylon material according to claim 1, characterized in that: The compatibilizer is POE-g-MAH.
6. The laser weldable nylon material according to claim 1, characterized in that: The auxiliary agent comprises 0.5-1 part of antioxidant and 0.5-1 part of lubricant.
7. The laser weldable nylon material according to claim 6, characterized in that: The antioxidant is antioxidant 1098, antioxidant 1076 or antioxidant 168.
8. The laser weldable nylon material according to claim 6, characterized in that: The lubricant is selected from one or more of stearic acid, stearic acid amide, oleic acid amide or lubricant EBS.
9. The method for preparing a laser-weldable nylon material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, adding nylon resin, anti-permeability modified nylon, compatibilizer and additive into a high-speed mixer and mixing for 15-20 minutes, and obtaining a mixed raw material after mixing evenly; S2, adding the mixture obtained in step S1 to a co-rotating twin-screw extruder for extrusion granulation, adopting a melt blending extrusion process, adding a blend of nylon resin, anti-permeability modified nylon, compatibilizer and processing aid from the main feed port, adding modified glass fiber from the side feed port, and after melt blending, cooling, air drying and granulation, the mixture is obtained.
10. The method for preparing a laser-weldable nylon material according to claim 9, characterized in that: The temperatures of each zone of the twin-screw extruder are as follows: zone one temperature 150-230°C, zone two temperature 180-265°C, zone three temperature 190-275°C, zone four temperature 200-280°C, zone five temperature 200-280°C, zone six temperature 200-280°C, and die head temperature 200-280°C; vacuum is turned on and the speed is 250-350r / min.
Citation Information
Patent Citations
Polyamide composition as well as preparation method and application thereof
CN111875957A
Polyamide resin composition as well as preparation method and application thereof
CN112724668A